Efektivitas Pendekatan Saintifik Berbasis Proyek terhadap Keterampilan Berpikir Kreatif dan Kemampuan Siswa dalam Pemecahan Masalah Kimia: The Effectiveness of a Project-Based Scientific Approach on Creative Thinking Skills and Students Chemistry Problem-Solving Ability - Handayani, Dwi; U.S, Supardi (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Chemistry learning in high school is still dominated by conventional approaches that inadequately develop creative thinking skills and problem-solving abilities. This study aims to examine the effectiveness of a project-based scientific approach on the creative thinking skills and chemistry problem-solving ability of senior high school students. The study utilized a quasi-experimental design with an experimental group that implemented the project-based scientific approach and a control group that used conventional learning. The research sample consisted of 68 eleventh-grade students divided into two groups. Research instruments included a creative thinking skills test, a chemistry problem-solving ability test, learning observation sheets, and a student response questionnaire. The results showed a significant difference in the post-test scores for creative thinking skills (t=4.87, p